PENGELOLAAN CORPORATE SOCIAL RESPONSIBILITY PT. LONSUM DI KECAMATAN UJUNG LOE KABUPATEN BULUKUMBA - Almuhajir Haris; Abdul Kadir Adys; Andi Luhur Prianto (Otoritas : Jurnal Ilmu Pemerintahan, 2014)
This paper aims to look at the management and the benefits of CSR (Corporate Social Responsibility) PT Lonsum in District Ujung Loe Bulukumba. The method used in this penelitiian is a qualitative description of the approach. The sample in this study as many as 10 people. Data collection techniques in this research is observation, interview, and documentation. The results showed that (a) planning conducted by PT. LonSum in doing a CSR (Corporate Social Responsibility) are correct (b) Implementation of CSR (Corporate Social Responsibility) is felt directly by the people. (C) Supervision in CSR (Corporate Social Responsibility) involved by the government and society (d) The effectiveness of the activity of management of CSR (Corporate Social Responsibility) directional well. (E) The benefits to society kec, Ujung Loe. Kab. Bulukumba. Give benefits in the field of improving the local economy, community empowerment and environmental safety. Tulisan ini bertujuan untuk melihat pengelolaan dan manfaat CSR (Corporate Social Responsibility) PT Lonsum di Kecamatan Ujung Loe Kabupaten Bulukumba. Metode yang digunakan dalam penelitiian ini adalah pendekatan deskripsi kualitatif. Sampel dalam penelitian ini sebanyak 10 orang. Teknik pengumpulan data dalam penelitian ini adalah observasi, wawancara, dan dokumentasi. Hasil penelitian menunjukkan bahwa (a) Perencanaan yang dilakukan oleh PT. LONSUM dalam melakukan suatu kegiatan CSR (Corporate Social Responsibility) sudah tepat (b) Pelaksanaan kegiatan CSR (Corporate Social Responsibility) dirasakan langsung oleh masyarakat. (c) Pengawasan dalam kegiatan CSR (Corporate Social Responsibility) melibatkan oleh pihak pemerintah dan masyarakat (d) Efektifitas pengelolaan kegitan CSR (Corporate Social Responsibility) terarah dengan baik. (e) Manfaat pada masyarakat kec, Ujung Loe. Kab. Bulukumba. Sangat memberikan manfaat dalam bidang peningkatan ekonomi masyarakat, pemberdayaan masyarakat dan keselamatan lingkungan.